Comparison of the structural and dynamical properties of holo and apo bovine alpha-lactalbumin by NMR spectroscopy. - Wijesinha-Bettoni, R; Dobson, C; Redfield, C (2001)
In the presence of 0.5 M NaCl at pH 7.1, the Ca(2+)-free apo form of recombinant bovine alpha-lactalbumin (BLA) is sufficiently stabilised in its native state to give well-resolved NMR spectra at 20 degrees C. The (1)H and (15)N NMR resonances of native apo-BLA have been assigned, and the chemical-shifts compared with those of the native holo protein. Large changes observed between the two forms of BLA are mainly limited to the Ca(2+)-binding region of the protein. These data suggest that Na(+) stabilises the native apo state through the screening of repulsive negative charges, at the Ca(2+)-binding site or elsewhere, rather than by a specific interaction at the vacant Ca(2+)-binding site. The hydrogen exchange protection of residues in the Ca(2+)-binding loop and the C-helix is reduced in the apo form compared to that in the holo form. This indicates that the dynamic behaviour of this region of the protein is substantially increased in the absence of the bound Ca(2+). Real-time NMR experiments show that the rearrangements of the structure associated with the conversion of the holo to apo form of the protein do not involve the detectable population of partially unfolded intermediates. Rather, the conversion appears to involve local reorganisations of the structure in the vicinity of the Ca(2+)-binding site that are coupled to the intrinsic fluctuations in the protein structure.